A proposal for a brazilian basic public education value chain (Research, Society and Development, 2021)
This study engaged in a value chain model for Brazilian basic public education. For that, we used Porter's value creation analysis proposal, in order to identify the primary and secondary activities of this chain. The methodological procedure adopted was a literature review, in which publications related to the topic were read in detail, in order to capture the nuances of the processes carried out in the context of providing public educational services capable of generating value. The result of the investigation into risks proposes a chain formed by two secondary activities (A.S) and two primary activities (A.P): (A.S.1) Regulation and Planning; (A.S.2) Evaluation and Monitoring; (A.P.1) School Management; (A.P. 2) Pedagogical Practices.